Extracellular superoxide dismutase, nitric oxide, and central nervous system O2 toxicity. - Oury, T D (1992)
Although reactive O2 species appear to participate in central nervous system (CNS) O2 toxicity, the exact roles of different reactive O2 species are undetermined. To study the contribution of extracellular superoxide anion (O2-) to CNS O2 toxicity we constructed transgenic mice overexpressing human extracellular superoxide dismutase (ECSOD; superoxide:superoxide oxidoreductase, EC 1.15.1.1) in the brain. Remarkably, when exposed to 6 atm (1 atm = 101.3 kPA) of hyperbaric oxygen for 25 min, transgenic mice demonstrated higher mortality (83%) than nontransgenic litter-mates (33%; P < 0.017). Pretreatment with diethyldithiocarbamate, which inhibits both ECSOD and Cu/Zn superoxide dismutase (Cu/Zn SOD) activity, increased resistance to CNS O2 toxicity, in terms of both survival (100% in transgenics and 93% in nontransgenics) and resistance to seizures (4-fold increase in seizure latency in both transgenic and nontransgenic mice; P < 0.05). Thus, O2- apparently protects against CNS O2 toxicity. We hypothesized that O2- decreased toxicity by inactivating nitric oxide (NO.). To test this, we inhibited NO. synthase (EC 1.14.23) with N omega-nitro-L-arginine to determine whether NO. contributes to enhanced CNS O2 toxicity in transgenic mice. N omega-nitro-L-arginine protected both transgenic and nontransgenic mice against CNS O2 toxicity (100% survival and a 4-fold delay in time to first seizure; P < 0.05), as well as abolishing the difference in sensitivity to CNS O2 toxicity between transgenic and nontransgenic mice. These results implicate NO. as an important mediator in CNS O2 toxicity and suggest that ECSOD increases CNS O2 toxicity by inhibiting O2(-)-mediated inactivation of NO.